Efficacy of Different Priming Methods on Germination and Growth of French Bean (Phaseolus vulgaris L.) Under Field Conditions in Mugu, Nepal - Shrestha, Saroj; Gyawali, Saurav; Dinesh Regmi; Supriya Chaulagain (International Journal of Applied Sciences and Biotechnology, 2024)
Low seed germination and poor growth have been major problems in French bean production in the hilly region of Nepal. An effective solution may lie in seed priming, which enhances rapid and uniform seed emergence, thereby improving yield. A field experiment was conducted to find out the effect of different seed priming methods on various varieties of French beans under field conditions in Chhaayanath Rara-4, Mugu, Nepal. The experiment was conducted in two factorial RCBD with three replications. Factor A was three French bean varieties; black, ghoratte, and red beans, and Factor B included two methods of priming; hydro and halo along with control. The results revealed that the germination parameter was significantly influenced by the method of priming and it was found non-significant in the case of varieties. Maximum germination percentage and higher speed of germination were found in seeds treated with hydro-priming. Similarly, the growth parameter was found significant for both varieties as well as priming methods. Vegetative growth parameters such as plant height, number of leaves, and number of primary and secondary branches were found significantly higher in hydro-primed seeds and ghoratte variety. Likewise, the yield parameters such as days to first flowering, days to 50% flowering, and yield per hectare were found significantly higher in hydro-primed ghoratte beans. Hence, hydro-priming can be used as a simple and cost-effective technique to improve germination and growth of French beans along with suitable variety under field conditions in Mugu district, Karnali province, Nepal. Int. J. Appl. Sci. Biotechnol. Vol 12(3): 137-144.